THE GOVERNANCE OF THE DISTRIBUTION OF DISASTER SURVIVOR LOGISTICAL ASSISTANCE (STUDY ON THE MAKASSAR FLOOD DISASTER IN SOUTH SULAWESI) - Siki, Martinus (LPSDI Bina Patria, 2023)
This study aims to analyze the governance of the distribution of disaster survivor logistical assistance from 1) Planning and needs determination functions; 2) Budgeting Function; 3) Procurement Function: 4) Storage and Distribution Function: 5) Maintenance Function: 6) Removal Function, and 7) Control Functions, a study on the Makassar flood disaster in South Sulawesi. This research is qualitative with a case study method that explores the governance of the distribution of disaster survivor logistical assistance (Study on the Makassar flood disaster, South Sulawesi). Using primary and secondary data obtained during the study by conducting in-depth interviews using interview guidelines. The results showed that the governance of the distribution of disaster survivor logistics assistance was less effective with various obstacles in the aspects of planning and needs, budgeting, procurement, distributions, maintenance, and controls so that the receipt of logistical assistance for disaster survivors was considered very slow. The limitations of this research are focused on the governance of the Regional Disaster Management Agency, Makassar City Government and Central Sulawesi Provincial Government in the implementation of the distribution of logistical assistance for flood survivors. The results of this study are expected to provide input for the Makassar City Government and the South Sulawesi Provincial Government as well as the Regional Disaster Management Agency to improve public services, especially in terms of disaster management and the distribution of effective and optimal logistical assistance. In addition, it is hoped that this research can be used as a reference for further research by taking the topic of disaster